AQUADATA: A work package of the Resilient Aquatic Food Systems Initiative - Rossignoli, Cristiano (WorldFish, 2022)
Presentation held at the FishBase - SeaLifeBase Symposium on the Approach to Data developed by the AqFs Initiative and possible synergies with FishBase and SeaLifeBase.